EDUCATIONAL STRATEGIES OF TECHNICAL PROFILE STUDENTS' ENGAGEMENT FOR EFFECTIVE LEARNING - Razikova Dilfuza Salixovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The article gives a brief outline of the efficacy of various modern learning strategies in higher education, aiming to demonstrate their significant impact on student engagement and academic achievement. The research is based on the idea that modern pedagogical technologies implemented nowadays are more functional and motivating than previous methods of teaching. Through a comprehensive examination of diverse active learning techniques and their implementation across different disciplines, this research seeks to provide empirical evidence supporting the adoption and integration of active learning practices into pedagogical approaches, ultimately contributing to the enhancement of student learning outcomes and overall educational quality.